Legal case books (1906)
3 ms. volumes of legal case summaries. One volume includes an index of "leading cases" with corresponding page numbers. Inserted in another volume are two newspaper clippings reporting on murder cases. One is dated 1906 and the other June 12 [no year] and refers to London. The case summaries refer to several Acts of Parliament dating from ca. 1874- ca. 1895.
Manuscript reference no. : NLA MS 969.
Keywords: Law -- Cases